2020
DOI: 10.1103/physrevresearch.2.033237
|View full text |Cite
|
Sign up to set email alerts
|

One-dimensional cell motility patterns

Abstract: During migration, cells exhibit a rich variety of seemingly random migration patterns, which makes unraveling the underlying mechanisms that control cell migration a difficult challenge. For efficient migration, cells require a mechanism for polarization, so that traction forces are produced in the direction of motion, while adhesion is released to allow forward migration. To simplify the study of this process, cells have been studied when placed along one-dimensional tracks, where single cells exhibit both sm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
106
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 58 publications
(110 citation statements)
references
References 42 publications
4
106
0
Order By: Relevance
“…This positive feedback can be described by the same set of equations previously proposed in refs. 20 , 21 , and naturally explains many of the observations reported above.…”
Section: Resultssupporting
confidence: 62%
See 4 more Smart Citations
“…This positive feedback can be described by the same set of equations previously proposed in refs. 20 , 21 , and naturally explains many of the observations reported above.…”
Section: Resultssupporting
confidence: 62%
“…We showed that such a run-and-tumble behavior can arise naturally in our theoretical model ( SI Appendix , Fig. S7 B ) ( 21 ), in a regime when both polarized and unpolarized states can develop.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations